A study on behavior, professional development and motivational quality of faculty of college of nursing in Olivarez College s.y. 2007-2008 - Pascual, Mary Jane; Real, Joyce; Nofuente, Mary Grace (Paranaque City; Olivarez College, 2008)
BRIEF INTRODUCTON OF THE STUDY: Education is one of the most important things to accomplish by an individual. This is possible with the help of our teachers or professors who mold us in the world of knowledge and learning. We see them as our models to guide us for a better future. In the world today, there are many changes that occur in having a good teaching techniques and new challenges to overcome to be professionally involved in the world of modern education. Teachers need not to be exposed only for reforms but also for opportunity where they can continually know what is currently new for students and also for him/her. Educators must enhance their personal needs to be a better guidance and to have a successful career in teaching because students depend on how teachers mold their innocent minds for new knowledge and learning's. Motivation is needed so that they will be encouraged to grow and eventually perform their jobs more effectively. A motivated person will work harder and persevere longer than the unmotivated one. Behavior is also important because one can have a better career in teaching by knowing how his/ her can control the good and bad traits in this profession. STATEMENT OF THE PROBLEM: The purpose of this study was to identify the behavioral, developmental, and motivational needs of the faculty of Olivarez College school year 2007-2008. Specifically, this study sought to answer the following questions: 1. What is the profile of the faculty in terms of the following needs? 1.1 Behavioral 1.2 Developmental 1.3 Motivational SUMMARY OF METHODOLOGY: This chapter deals with the detailed discussion of making the study. This includes the research design of the study, subjects/ respondents, the research instrument, and the data gathering procedure and the data analysis In this study, we adopted the descriptive analytical method of research. According to Polit(1995) descriptive method of research reinforced by interview and documentary analysis was use in this research study. The purpose of descriptive studies is to observe, describe and document aspects of a situation as it naturally occurs and sometimes to serve as a starting point for hypothesis, general or theory development. The survey analyzed the data of faculty needs of the Nursing College department, the degree on which these needs were met. The respondents of this study are the full time faculty members of the Health Related Sciences Department of Olivarez College. SUMMARY OF FINDINGS 1. Intrinsic Motivational needs are the highest priority as perceived by the nursing faculty in Olivarez College. Intrinsic motivational needs as the top priority re- affirmed the fact that the teacher's focus of attention is their satisfaction of their inner wanting as an educator. They prioritize more of their inner satisfaction regarding their work rather than the extrinsic factor which prioritize incentives, rewards etc. 2. Behavioral needs are the second highest priority which means that the effectively rate as a teacher In this institution is high as well as the surroundings the teachers main task is to create conditions that will encourage and stimulate learning, the educators of this institution met this quality of needs teachers skills and attitudes influences everything that happens in their classrooms. 3. Nursing faculty of Olivarez college recognize that the function of there seminars and meeting is important for their career not only today but also in the future CONCLUSION Motivation refers to getting someone moving as proven in the finding of this research in the Nursing Faculty of Olivarez College. The findings revealed that the nursing faculty considered the motivational needs as their highest priority. It is also revealed that internal stimulus to learning, fringe benefits and inner satisfaction or are very well essential in their performance for everyday living along with the other needs in order to work efficiently and effectively as person and as educator. RECOMMENDATIONS 1. The school administration should implement a more realistic and feasible program, which will give its teachers a good chance for professional growth like pursuing their masteral/doctoral degrees. 2. There should be a more intensive school program of activities to promote better camaraderie among teachers like giving newly employed faculty members the chance to lead a school activity as a means of recognizing or discovering their potential. Recognition from peers based on one's capabilities will help boost the morale of the teacher and thereby create in him the feeling of being socially accepted. Feelings of insecurity from the older members of the faculty should be erased. They should help assist the young teachers to adjust to the work force. 3. School administrators should be sensitive to the economic needs of its employees particularly the teachers. An adage says that only contented cows can give the best milk. This is also true to teachers. 4. The faculty must reprioritize all the three needs for a quality and effective teaching career.
Undergraduate Thesis